2013
DOI: 10.3233/cbm-130371
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of circulating cell-free DNA recovery for KRAS mutation and HPV detection in plasma

Abstract: Data presented in this study facilitate detection of tumour-specific cfDNA and improve standards needed for the implementation of cfDNA technology into routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…10 To measure the circulating cell-free DNA (cfDNA) concentration in blood plasma, amplification of human telomerase reverse transcriptase (TERT) was performed. DNA was extracted from plasma (1 mL) as described previously.…”
Section: Quantification Of Dna Vls In Plasma (Chpv16 Dna Vls)mentioning
confidence: 99%
See 2 more Smart Citations
“…10 To measure the circulating cell-free DNA (cfDNA) concentration in blood plasma, amplification of human telomerase reverse transcriptase (TERT) was performed. DNA was extracted from plasma (1 mL) as described previously.…”
Section: Quantification Of Dna Vls In Plasma (Chpv16 Dna Vls)mentioning
confidence: 99%
“…DNA was extracted from plasma (1 mL) as described previously. 10 To measure the circulating cell-free DNA (cfDNA) concentration in blood plasma, amplification of human telomerase reverse transcriptase (TERT) was performed. 10 Each measurement consisted of a standard curve, a negative control, and the experimental sample.…”
Section: Quantification Of Dna Vls In Plasma (Chpv16 Dna Vls)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent progress in the analysis of blood samples for circulating tumor cells or cell-free circulating tumor DNA (ctDNA) has shown that liquid biopsies may have potential applications in the detection and monitoring of cancer [9][10][11]. Similarly, in a study on cervical cancer, ctDNA has become a major focus, providing a strong basis for early diagnosis and 4 prognosis in cervical cancer [10,12,13]. Cervical cancer is typically caused by high-risk HPVs (hrHPVs), primarily genotypes 16 and 18 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified a correlation between fcDNA and cancer, including ovarian, uterine, colorectal, breast, lung and prostate cancer, cervical and malignant gastrointestinal tumors, glioma, hepatocellular carcinoma, metastatic melanoma, leukemia and lymphoma (8–13). The characteristics of fcDNA may also make this type of DNA a promising tool for the diagnosis of early-stage EOC.…”
Section: Introductionmentioning
confidence: 99%